2013
DOI: 10.1080/08997764.2013.785553
|View full text |Cite
|
Sign up to set email alerts
|

Do Newspapers Matter? Short-Run and Long-Run Evidence From the Closure ofThe Cincinnati Post

Abstract: The Cincinnati Post published its last edition on New Year's Eve 2007, leaving the Cincinnati Enquirer as the only daily newspaper in the market. The next year, fewer candidates ran for municipal office in the Kentucky suburbs most reliant on the Post, incumbents became more likely to win reelection, and voter turnout and campaign spending fell. These changes happened even though the Enquirer at least temporarily increased its coverage of the Post's former strongholds. Voter turnout remained depressed through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(25 citation statements)
references
References 16 publications
0
25
0
Order By: Relevance
“…It follows that when local newspapers fold, citizen engagement suffers. A case study by Schulhofer-Wohl and Garrido (2013) examined political effects of the closing of the Cincinnati Post , a small newspaper that served the northern Kentucky suburbs of the region and went out of print in 2007. The study analyzed data from municipalities that made up the core circulation area of the Cincinnati Post .…”
Section: Newspapers and Governmentmentioning
confidence: 99%
See 1 more Smart Citation
“…It follows that when local newspapers fold, citizen engagement suffers. A case study by Schulhofer-Wohl and Garrido (2013) examined political effects of the closing of the Cincinnati Post , a small newspaper that served the northern Kentucky suburbs of the region and went out of print in 2007. The study analyzed data from municipalities that made up the core circulation area of the Cincinnati Post .…”
Section: Newspapers and Governmentmentioning
confidence: 99%
“…Although past research has found important consequences of weak or absent newspapers, none to our knowledge have systematically examined the effects of shrinking newsrooms on local political outcomes over time and across multiple cities. In addition, many of the more recent studies have used the rather blunt measure of newspaper closure (e.g., Schulhofer-Wohl and Garrido 2013). Previous work suggests the sharp and sustained decline in newsroom staffing that began in 2006 would have had important consequences for local politics.…”
Section: Newspapers and Governmentmentioning
confidence: 99%
“…Nonetheless, the variation in media scrutiny that has been observed (e.g., Arnold 2004;Fogarty 2008;Schaffner 2006), including at the state level (Campante and Do 2014;Carpini, Keeter, and Kennamer 1994), seems to be consequential. It has been shown that coverage of legislators at both the state and federal level can have significant consequences for citizen political knowledge (Carpini, Keeter, and Kennamer 1994), the incumbency advantage in elections (Gentzkow, Shapiro, and Sinkinson 2011;Prior 2006;Schulhofer-Wohl and Garrido 2013), legislator behavior in office (Hogan n.d.;Snyder and Strömberg 2010), and state-level corruption (Campante and Do 2014). We argue that the threat of fact-checking has the potential to create career risks for politicians by generating negative coverage that could damage their reputation and credibility and thereby harm their prospects for reelection, entering party leadership, or seeking higher office.…”
Section: The Effect Of Fact-checking On Politiciansmentioning
confidence: 99%
“…In this case, then, an active choice would operate in seeking the most appreciated information, as held for example, by [7,49,68]. This debate is not being put forward here: what matters, for our purposes, is the evidence that news media affect electoral participation of citizens, as shown by [67,56,64,41,63,33], among others. For example, as explained in [27], social networks may help in recognizing the political orientation on the basis of the shared contents.…”
Section: Introductionmentioning
confidence: 99%